Estimating Light Acclimation Parameters of Cucumber Leaves Using Time-Weighted Averages of Daily Photosynthetic Photon Flux Density - Yu, Liyao; Fujiwara, Kazuhiro; Matsuda, Ryo (Frontiers in Plant Science, 2022)
Leaves acclimate to day-to-day fluctuating levels of photosynthetic photon flux density (PPFD) by adjusting their morphological and physiological parameters. Accurate estimation of these parameters under day-to-day fluctuating PPFD conditions benefits crop growth modeling and light environment management in greenhouses, although it remains challenging. We quantified the relationships between day-to-day PPFD changes over 6 days and light acclimation parameters for cucumber seedling leaves, including leaf mass per area (LMA), chlorophyll (Chl) a/b ratio, maximum net photosynthetic rate (Pnmax), maximum rate of ribulose-1,5-bisphosphate (RuBP) carboxylase/oxygenase (Vcmax), and maximum rate of electron transport (Jmax). The last two parameters reflect the capacity of the photosynthetic partial reactions. We built linear regression models of these parameters based on average or time-weighted averages of daily PPFDs. For time-weighted averages of daily PPFDs, the influence of daily PPFD was given a specific weight. We employed three types of functions to calculate this weight, including linear, quadratic, and sigmoid derivative types. We then determined the trend of weights that estimated each parameter most accurately. Moreover, we introduced saturating functions to calibrate the average or time-weighted averages of daily PPFDs, considering that light acclimation parameters are usually saturated under high PPFDs. We found that time-weighted average PPFDs, in which recent PPFD levels had larger weights than earlier levels, better estimated LMA than average PPFDs. This suggests that recent PPFDs contribute more to LMA than earlier PPFDs. Except for the Chl a/b ratio, the average PPFDs estimated Pnmax, Vcmax, and Jmax with acceptable accuracy. In contrast, time-weighted averages of daily PPFDs did not improve the estimation accuracy of these four parameters, possibly due to their low response rates and plasticity, indicating that daily PPFD levels might have equal influence on these parameters for a duration of 6 days. Calibrating functions generally improved estimation of Chl a/b ratio, Vcmax, and Jmax, because of their saturating tendencies under high PPFDs. Our findings provide a reasonable approach to quantifying the extent to which leaves acclimate to day-to-day fluctuating PPFDs, especially the extent of LMA.